Digital yuan : politicisation of China's CBDC - Loh, Dylan Ming Hui (2021)
Global interest in cryptocurrencies and private stablecoin developments have compelled central banks around the world to consider developing their own digital sovereign currencies. China is leading the pack with the digital yuan. The race to launch the world’s first major central bank digital currency (CBDC) and its politicisation signal the start of a subtle competition between major economies.